2019
DOI: 10.1016/j.jot.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of location and mode of failure in three screw fixations for a comminuted transforaminal sacral fracture model

Abstract: BackgroundPelvic ring–comminuted transforaminal sacral fracture injuries are rotationally and vertically unstable and have a high rate of failure.ObjectiveOur study purpose was to use three-dimensional (3D) optical tracking to detect onset location of bone–implant interface failure and measure the distances and angles between screws and line of applied force for correlation to strength of pelvic fracture fixation techniques.Methods3D relative motion across sacral–rami fractures and screws relative to bone was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The TriFix screw is equivalent to a reinforced fixation anchor in the iliac bone. Therefore, failures such as the washer penetration described are virtually impossible [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TriFix screw is equivalent to a reinforced fixation anchor in the iliac bone. Therefore, failures such as the washer penetration described are virtually impossible [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18] Synthetic bone models have been used in numerous recent biomechanical studies of the pelvis. [14,15,19,22] They allow for consistent comparisons by eliminating the variability seen among cadaver specimens because of disease, diet, age, sex, and a host of other factors. Simonian et al [25][26][27] in their comparison of multiple plate fixation methods found significant reduction in motion with all plate constructs but supraphysiological motion in all but a "box plate" construct.…”
Section: Discussionmentioning
confidence: 99%
“…We created a single-leg stance model similar to previously described models, [14,[19][20][21][22] with elements used from other biomechanical models. [19,20,23,24] Each pelvis was securely attached to the material testing system (Bionix 858, MTS, Eden Prairie, MN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical investigations showed that two unilateral screws in S1 generate less cut-out and allow more load cycles in the finite-element model [15,29] and have less risk of neurological injury compared to screws in S2 [25,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%